2014
DOI: 10.1080/02508060.2014.978972
|View full text |Cite
|
Sign up to set email alerts
|

One step at a time: international law and the duty to cooperate in the management of shared water resources

Abstract: Analyzing the dynamics of international cooperation, this article describes the role of international law in the process. It illustrates that international law is a tool to achieve mutually beneficial relations and can be a driver for cooperation. Describing how these dynamics apply in the context of cooperation on transboundary rivers, the article traces the emergence of the general duty to cooperate in international water law as a legal response to the interdependence and coordination requirements in the man… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
12
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 24 publications
(12 citation statements)
references
References 8 publications
(6 reference statements)
0
12
0
Order By: Relevance
“…Cooperation is a step-by-step process that starts, for example, with the regular meetings of a joint committee and develops towards the in-depth nexus approach with intersectoral working and expert groups and public hearings. The essential building blocks of the cooperation are reciprocity and good faith between States as well as mutual benefits [27,30]. The nexus approach to the transboundary watercourses cooperation requires that riparian States perceive that the cooperation is in their common interests in the long term.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Cooperation is a step-by-step process that starts, for example, with the regular meetings of a joint committee and develops towards the in-depth nexus approach with intersectoral working and expert groups and public hearings. The essential building blocks of the cooperation are reciprocity and good faith between States as well as mutual benefits [27,30]. The nexus approach to the transboundary watercourses cooperation requires that riparian States perceive that the cooperation is in their common interests in the long term.…”
Section: Discussionmentioning
confidence: 99%
“…The principle of cooperation is one of the main features in international water law [29,30]. In the UN Watercourses Convention, it is stated that watercourse States shall cooperate on the basis of sovereign equality, territorial integrity, mutual benefit and good faith in order to attain optimal utilisation and adequate protection of an international watercourse (Art.…”
Section: Principle Of Cooperationmentioning
confidence: 99%
“…Therefore, there is a consensus that cooperative water resources planning and management in a trans-boundary river basin can provide opportunities to increase water benefits [4][5][6][7][8]. Phillips et al [4] suggested a policy context for shared responsibility and an institutional framework for analyzing shared benefits resulting from the corporation between countries.…”
Section: Introductionmentioning
confidence: 99%
“…This is particularly evident in the case of transboundary river basins in which unidirectional, negative externalities, caused by the upstream regulation of the natural flow, often place some parties at a disadvantage and result in asymmetric relationships that add to the challenge of coordinating resource use (van der Zaag, 2007). There is a consensus among water professionals that the cooperative management of shared river basins should provide opportunities to increase the scope and scale of benefits (Phillips et al, 2006;Grey and Sadoff, 2007;Leb, 2015), stepping beyond the volumetric allocation of water that reduces negotiations between riparians to a zero-sum game. In their seminal paper, Sadoff and Grey (2002) discussed the types of benefits that river basins can provide, assuming cooperation: benefits to the river can result from sustainable cooperative management of the ecosystem; efficient, cooperative management and development of river flow can yield benefits from the river in the form of increased water quality, quantity and productivity; policy shifts away from riparian disputes/conflicts toward cooperative development can reduce costs of noncooperation arising because of the river; and cooperation be-D. Arjoon et al: Benefit sharing tween riparian states can lead to economic, political and institutional integration, resulting in benefits beyond the river.…”
Section: Introductionmentioning
confidence: 99%